Paradigmatic Basics of Strategic Management - Vishnevsky, A.S. (Економічний вісник Донбасу, 2015)
The article presents the worldview prerequisites for the formation of strategy and the use of strategic management in companies, organizations and institutions. For this there was considered the present structure of the strategy as a product of the subject-object relations in space-time continuum. The hypothesis about accordance elements of strategic management with philosophical paradigms was formulated and proved. There were shown the impossibility of the creation of the Strategic Management (in its modern sense) in the era preceding the modernity and were described its formation in the logic of modernity. The adequacy using of current approaches to strategic management in logic of postmodernism was doubted. Because this paradigm involves the revision of the subject-object relationship and displacement from real space to virtual space. In conclusion considers the possibility adaptation of modern strategic management to the logic of postmodernism. У статті досліджено світоглядні передумови формування стратегії та використання стратегічного управління в компаніях, організаціях та установах. Для цього розглянута сучасна структура стратегії, як продукт суб'єкт-об'єктних відносин в просторово-часовому континуумі. Сформульована і доведена гіпотеза залежності стратегічного управління від світоглядних інтерпретацій його окремих елементів. Продемонстровано неможливість зародження стратегічного управління (в сучасному його розумінні) в епоху, що передувала модерну, і обґрунтовано його формування в межах логіки модерну. Ставиться під сумнів можливість адекватного застосування сучасних підходів до стратегічного управління в рамках подальшого укорінення логіки постмодерну, яка передбачає перегляд суб'єкт-об'єктних відносин та зміщення реального простору в бік віртуального. У заключній частині розглядаються можливості адаптації сучасного стратегічного управління до логіки постмодерну. В статье исследованы мировоззренческие предпосылки формирования стратегии и использования стратегического управления в компаниях, организациях и учреждениях. Для этого рассмотрена современная структура стратегии, как продукта субъект-объектных отношений в пространственно-временном континууме. Сформулирована и доказана гипотеза зависимости стратегического управления от мировоззренческих интерпретаций его отдельных элементов. Показана невозможность зарождения стратегического управления (в современном его понимании) в эпоху предшествующую модерну и обосновано его формирование в рамках логики модерна. Ставится под сомнение возможность адекватного применение современных подходов к стратегическому управлению в рамках дальнейшего укоренении логики постмодерна, которая предполагает пересмотр субъект-объектных отношений и смещение реального пространства в сторону виртуального. В заключении рассматриваются возможности адаптации современного стратегического управления к логике постмодерна.